2009
DOI: 10.1038/mp.2009.120
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia and DYX1C1: deficits in reading and spelling associated with a missense mutation

Abstract: The status of DYX1C1 (C15q21.3) as a susceptibility gene for dyslexia is unclear. We report the association of this gene with reading and spelling ability in a sample of adolescent twins and their siblings. Family-based association analyses were carried out on 13 single-nucleotide polymorphisms (SNPs) in DYX1C1, typed in 790 families with up to 5 offspring and tested on 6 validated measures of lexical processing (irregular word) and grapheme-phoneme decoding (pseudo-word) reading-and spelling-based measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 56 publications
7
67
0
3
Order By: Relevance
“…It is possible that this gene represents a genuine dyslexia risk gene and that common risk variants in DYX1C1 are contributing to the phenotype, as supported also by associations with reading and spelling in an unselected adolescent cohort from Australia. 15 However, it might be also possible that high-penetrance mutations in DYX1C1 or in the other dyslexia candidate genes are only present in some familial cases. In this case, a deep-sequencing approach in families with dyslexia would be more appropriate to find an enrichment of such highpenetrance private mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that this gene represents a genuine dyslexia risk gene and that common risk variants in DYX1C1 are contributing to the phenotype, as supported also by associations with reading and spelling in an unselected adolescent cohort from Australia. 15 However, it might be also possible that high-penetrance mutations in DYX1C1 or in the other dyslexia candidate genes are only present in some familial cases. In this case, a deep-sequencing approach in families with dyslexia would be more appropriate to find an enrichment of such highpenetrance private mutations.…”
Section: Discussionmentioning
confidence: 99%
“…DYX1C1 has also been associated with reading and spelling ability in a large unselected group of adolescents from Australia. 15 Furthermore, it has been shown that dyslexia-associated variants within the promoter region of DYX1C1 16 influence the binding affinity of transcription factor complexes. 17 Two genes have been reported to be associated with dyslexia within the linkage region on chromosome 6p22.2: DCDC2 (doublecortin domain-containing protein 2, MIM 605755) [18][19][20] and KIAA0319 (MIM 609269).…”
Section: Introductionmentioning
confidence: 99%
“…Two independent Australian cohort studies also performed quantitative analyses of reading and reading related measures in population-based samples [Bates et al, 2010;Paracchini et al, 2011]. Bates et al [2010] found three SNPs that were significantly associated with different measures: rs685935 with short-term memory; rs17819126 with irregular reading, nonword reading, and irregular spelling; and rs3743204 with nonword reading. Paracchini et al [2011] found that spelling was associated with the three markers rs7174102, rs8043049, and rs8037376, and reading associated with rs8040756.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies did not find association between DYX1C1 SNPs and quantitative reading tasks [Scerri et al, 2004;Meng et al, 2005]. Two independent Australian cohort studies also performed quantitative analyses of reading and reading related measures in population-based samples [Bates et al, 2010;Paracchini et al, 2011]. Bates et al [2010] found three SNPs that were significantly associated with different measures: rs685935 with short-term memory; rs17819126 with irregular reading, nonword reading, and irregular spelling; and rs3743204 with nonword reading.…”
mentioning
confidence: 99%
See 1 more Smart Citation